The Patterns of Banditry in the Specific Geopolitical Region in Nigeria - Paul Irabor (Acta Politica Polonica)
This paper aims to prove that banditry exists across Nigeria’s geopolitical regions, evolving into distinct characteristics that define the security situations in these regions. The objectives of the study are to examine the patterns of banditry in Nigeria’s geopolitical regions and to suggest methods to curb it. Relying on secondary data and systematic analysis, the study’s findings demonstrate the various ways that banditry has taken shape throughout Nigeria’s geopolitical regions. These include insurgency in the North-East, ethnic/religious conflict between Hausa farmers and Fulani herders in the North-Central, herder-farmer conflict, criminal gang violence and insurgency in the North-West, separatist violence and herder-farmer conflict in the South-East, militancy, and herder-farmer conflict in the South-South as well as urban crime and herder-farmer conflict in the South-West. The study suggests regional security measures through decentralisation of the security system to control the complex nature of banditry in Nigeria.